2014
DOI: 10.5152/tjg.2014.3255
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma presenting as a huge intra-abdominal mass: A case report

Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver and is generally associated with hepatitis B or C virus-related cirrhosis. A giant intra-abdominal HCC mass that fills nearly the whole abdomen is not often reported in the literature. In this report, we present a case in which a patient with hepatitis B developed a giant intra-abdominal mass that originated from segment three of the liver and infiltrated the stomach and transverse colon. We were able to resect the tumor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Sites of the lower part of the gastrointestinal tract, such as the colon, jejunum, ileum and rectum were also less affected. In exceptional cases, a liver tumor can simultaneously involve more than one segment of the GI tract [7,51,58,59,65,66,80].…”
Section: Discussionmentioning
confidence: 99%
“…Sites of the lower part of the gastrointestinal tract, such as the colon, jejunum, ileum and rectum were also less affected. In exceptional cases, a liver tumor can simultaneously involve more than one segment of the GI tract [7,51,58,59,65,66,80].…”
Section: Discussionmentioning
confidence: 99%
“…direct-acting antiviral drugs questioned the impact of those drugs on the occurrence or recurrence of HCC in patients with HCV related cirrhosis. [3,[7][8][9] Such finding was not seen in other cases treated with interferon-based regimens, and this endorsed specialists to propose that those drugs may play a significant role in the development of HCC. [3,8,9] On the other hand, other studies have reported the opposite effect of direct-acting antiviral drugs on HCC occurrence or recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[7][8][9] Such finding was not seen in other cases treated with interferon-based regimens, and this endorsed specialists to propose that those drugs may play a significant role in the development of HCC. [3,8,9] On the other hand, other studies have reported the opposite effect of direct-acting antiviral drugs on HCC occurrence or recurrence. [10,11] The relationship between direct-acting antiviral agents and HCC occurrence or recurrence and the underlying possible mechanisms remain controversial and there is no enough evidence to prove or disprove this relationship.…”
Section: Introductionmentioning
confidence: 99%